Semi-Passive RFID Development Platform for Implementing and Attacking Security Tags. Issue 1 (2012) - Plos, Thomas; Aigner, Manfred; Baier, Thomas; Feldhofer, Martin; Hutter, Michael; Korak, Thomas; Wenger, Erich
No abstract available